Urban artificial light emission function determined experimentally using night sky images. (September 2016) - Solano Lamphar, Héctor Antonio; Kocifaj, Miroslav
Abstract: To date, diverse approximations have been developed to interpret the radiance of a night sky due to light emissions from ground-based light sources. The radiant intensity distribution as a function of zenith angle is one of the most unknown properties because of the collective effects of all artificial, private and public lights. The emission function (EF) is, however, a key property in modeling the skyglow under arbitrary conditions, and thus it is equally required by modelers, light pollution researchers, and also experimentalists who are using specialized devices to study the diffuse light of a night sky. In this paper, we present the second generation of a dedicated measuring system intended for routine monitoring of a night sky in any region. The experimental technology we have developed is used to interpret clear sky radiance data recorded at a set of discrete distances from a town (or city) with the aim to infer the fraction of upwardly emitted light (F), that is a parameter scaling the bulk EF. The retrieval of the direct upward emissions has been improved by introducing a weighting factor that is used to eliminate imperfections of experimental data and thus to make the computation of F more stable when processing the radiance data taken at two adjacent measuring points. The field experiments made in three Mexican cities are analyzed and the differences found are discussed. Highlights: Radiance of a nightsky is determined as a function of distance to the city center. A simple device is developed and used for routine monitoring of a night sky. The fractions ( F ) of upwardly emitted light is retrieved for three Mexican cities. A stabilizing factor is introduced to eliminate imperfections of experimental data. The values of F are consistent with those retrieved during previous field campaigns.